WORKPLACE SPIRITUALITY IN ISLAMIC EDUCATIONAL INSTITUTIONS IN CENTRAL LAMPUNG REGENCY - kurniawan, wakib; Andrianto, Dedi; Mu’amalah, Husnul; Sari, Nurdiana; Najah, Safiratun (Journal of Management and Islamic Finance, 2025)
This study aims to validate a contextualized Islamic Workplace Spirituality Scale (IWSS) specifically designed for Islamic educational institutions in Indonesia. The instrument incorporates three core spiritual dimensions derived from Islamic teachings—taqorrub (devotion to Allah), muroqobah (spiritual self-awareness), and istiqomah (steadfastness)—which are operationalized into 10 measurable indicators. Using a cross-sectional survey, data were collected from 354 teachers across various Islamic education levels in Central Lampung Regency. The validity and reliability of the instrument were assessed using Exploratory and Confirmatory Factor Analysis (EFA and CFA) with SmartPLS 3.0. The results confirmed that the instrument is both valid and reliable, making it suitable for measuring workplace spirituality within Islamic education settings. Key findings indicate that teachers exhibit a high level of workplace spirituality, with taqorrub emerging as the strongest dimension. This suggests that spiritual values play a central role in shaping teachers’ professional behavior and motivation. The study underscores the importance of integrating spiritual development into human resource strategies to enhance organizational effectiveness and efficiency. However, its scope is limited to a single district, highlighting the need for broader studies across multiple regions or countries to increase generalizability